S141 Tumour Necrosis Factor Receptor 1 Shedding Is Related To Acute Skeletal Muscle Wasting In Critical Illness. (10th November 2014) - Puthucheary, ZA; Rawal, J; McPhail, MJW; Dew, T; Phadke, R; Rowlerson, A; Harridge, SDR; Montgomery, HE; Hart, N
Abstract : Introduction: Muscle wasting occurs early and rapidly in critically ill patients. It results from a decrease in muscle protein synthesis and an increase in its breakdown, with muscle necrosis a common associated finding. The drivers for such atrophy and necrosis remain poorly understood, as do the related regulatory pathways. We hypothesised that systemic and intracellular cytokines play a role in this process. Methods: The UK-MUSCLE study prospectively studied the wasting response (change in Rectus Femoris cross sectional area (RFCSA ) using serial ultrasound) in critically ill patients admitted to the ICU. Cytokine profiles (high sensitivity cytokine chip array, Randox, Ireland) were analysed in serum samples from 62 of these patients (days 1 and 7) and in contemporaneous Vastus Lateralis biopsies of 35 patients. Tumour Necrosis Factor (TNF)-α, TNF receptor (TNFR) 1 and 2, interleukin (IL)1a, il1b, IL-2, IL-4, IL-6, IL-8, IL-10, Vascular Endothelial growth Factor (VEGF), Interferon (IFN)-γ, Monocyte Chemoattractant Protein-1(MCP-1) and Epidermal Growth Factor were assayed. Muscle necrosis was determined by hematoxylin and eosin staining of the Vastus Lateralis biopsies. Results: Intramuscular TNFR1 concentrations increased over 7 days (0.83 ± 1.1 µg/L to 2.07 ± 2.65 µg/L; p = 0.042), as did intramuscular interleukin-10 (22.69 ± 26.5 ng/L to 59.8 ± 80.0 ng/L; p = 0.005). Increases in serum IL-1a (0.52 ± 0.26 ng/L to 0.57 ± 0.28 ng/L, p = 0.03), VEGF (166.86 ± 231.7 ng/L to 246.6 ± 236.7 ng/L, p < 0.001) and MCP-1 (886.8 ± 685.0 ng/L to 386.49 ± 469.7 ng/L, p < 0.001) were seen as well as a decrease in IL-6 (322.2 ± 422.7 ng/L to 78.55 ± 184.4 ng/L, p < 0.001), il-10 (22.73 ± 51.1 ng/L to 7.61 ± 15.3 ng/L, p = 0.03), IFN- γ (4.76 ± 11.0 ng/L to 1.28 ± 2.02 ng/L, p = 0.02) and MCP-1 (886.8 ± 685.0 ng/L to 386.49 ± 469.7 ng/L, p < 0.001). Neither myonecrosis nor change in RFCSA was related to that in intramuscular cytokines by linear and logistical-regression analysis, using 10% loss as a cut off. Loss in RFCSA over 10 days was very weakly correlated with serum TNFR1 concentration on days 1 (r 2 =0.12; p < 0.01) and 7 (r 2 =0.09; p = 0.02) and with serum IL-10 concentration (r 2 =0.19; p < 0.01). Myofibre necrosis was unrelated to serum cytokine profile. Discussion: Soluble TNFR1 is associated with the degree of muscle wasting in critical illness. This relationship may be causal as TNF1R signalling leads to activation of nuclear factor kappa beta and apoptosis. Whilst no evidence was seen for intramuscular inflammation, increased intramuscular IL-10 may be protective, in its anti-inflammatory role.